Etika Profesi Kependidikan dan Tanggung Jawab Guru Terhadap Peserta Didik - Osna Yenti; Agung Marta Pratama; Ken Hawari; M. Ali Basroh; Retno Wahyu Ningsih (STKIP Subang, 2026)
Professional ethics in education is the moral foundation that guides teachers in carrying out their duties and responsibilities professionally. Teachers not only act as instructors, but also as educators, mentors, and role models for students in the character-building process. This article aims to comprehensively examine professional ethics in education, teachers' responsibilities for student development, the role of teachers as ethical and moral role models, teachers' protection of students' rights, and various obstacles to the application of professional ethics in the educational environment. The method used is a literature review by examining various relevant sources, such as books, scientific journals, and laws and regulations in the field of education. The results of the study show that understanding and applying professional ethics in education greatly determines the quality of the learning process and the educational relationship between teachers and students. Teachers who uphold professional ethics are able to be fair, objective, responsible, and respect the rights and dignity of students. However, in practice, the application of professional ethics still faces various obstacles, such as limited understanding of ethics, high workloads, environmental pressures, and technological developments that require ethical adaptation. Therefore, a shared commitment between teachers, educational institutions, and other stakeholders is needed to strengthen the consistent application of professional ethics. With the proper application of professional ethics, it is hoped that quality education that is character-building and oriented towards the holistic development of students will be realized.